2020
DOI: 10.5671/ca.44.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Variations in Anthropometry, Body Composition and Nutritional Status among the Adult Kheria Sabar Males of Purulia, West Bengal, India

Abstract: Undernutrition and ageing may have a significant effect on body composition. A cross sectional study was conducted to explore the age-related variations among different anthropometric and body composition characteristics amongst the adult Kheria Sabar males of Purulia district of West Bengal. From fifteen villages, 304 apparently healthy adult males aged 18–60 years were selected at random. Subjects were categorized into four age groups and standard anthropometric measurements were used like height (HT), weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a similar study of Sabar males of Purulia district, Das et al explained that family size and family income influence the living standard specifically housing and sanitary condition should be better and should influence their health status. 1 The current study focuses on a similar association of family income with health status and nutritional level for Sabar people of Jhargram. 11,12 This study has revealed that education also influences the health status of Sabar tribes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study of Sabar males of Purulia district, Das et al explained that family size and family income influence the living standard specifically housing and sanitary condition should be better and should influence their health status. 1 The current study focuses on a similar association of family income with health status and nutritional level for Sabar people of Jhargram. 11,12 This study has revealed that education also influences the health status of Sabar tribes.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, age, nutrition, physical activity and hormonal status are the main determinants of body composition among healthy adults. 1 Undernutrition may have a significant effect on body composition as it develops due to nutritional deficiency which results in organ dysfunction, reduced body mass, abnormal blood chemistry and worsened clinical outcomes. 2 Sabar is one of the most backward tribal communities in West Bengal, traditionally living in the deep forest areas.…”
Section: Introductionmentioning
confidence: 99%